2006
DOI: 10.1002/hipo.20235
|View full text |Cite
|
Sign up to set email alerts
|

Restoring theta‐like rhythmicity in rats restores initial learning in the Morris water maze

Abstract: Neural activity often becomes rhythmic during mental processing. But there has been no direct proof that rhythmicity, per se, is important for mental function. We assessed this issue in relation to the contribution of hippocampal theta-frequency rhythmicity to learning in the Morris water maze by blocking theta (and other septal inputs to the hippocampus) and then using electrical stimulation to restore rhythmicity. We injected tetracaine into the medial septal area, and so blocked septal input to the hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
200
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(216 citation statements)
references
References 52 publications
(53 reference statements)
12
200
3
Order By: Relevance
“…It was suggested that restoring theta-range rhythmicity restores hippocampal function (McNaughton, Ruan, & Woodnorth, 2006). The theta rhythm may also play a role in information processing using an attentional double-gating mechanism, "filtering-in" signals for effective registration and encoding of selected information and additionally "filteringout" interfering inputs (Vinogradova, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that restoring theta-range rhythmicity restores hippocampal function (McNaughton, Ruan, & Woodnorth, 2006). The theta rhythm may also play a role in information processing using an attentional double-gating mechanism, "filtering-in" signals for effective registration and encoding of selected information and additionally "filteringout" interfering inputs (Vinogradova, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Since decreased and increased theta activity correlate with cognitive deficit and improvement, respectively (Kinney et al, 1999;Nolan et al, 2004;McNaughton et al, 2006), compromised theta activity during epileptogenesis could be an important contributing factor for cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…We also proved that arti cial replacement of blocked RSA repairs behavioural dysfunction [91] (the first proof that any EEG rhythmicity is functional in and of itself ); and that changes in RSA mediate the action of anxiolytics on behavioural inhibition in an approach-avoidance conflict [92]. Thus RSA appears to be not just a reliable model of anxiolytic action but to be a significant neural substrate of an anxietyrelated process.…”
Section: Rhythmical Slow Activity (Rsa Theta) As a Potential Anxietymentioning
confidence: 60%